A framework for public-private-people partnerships in the city resilience-building process. (December 2018) - Marana, Patricia; Labaka, Leire; Sarriegi, Jose Mari
Highlights: A public-private-people partnership framework to improve city resilience is presented. A literature review on partnerships and city resilience is exhibited. A set of 16 relevant characteristics have been defined in the framework. The characteristics are classified into three dimensions and three layers. Existing interdependencies between the different characteristics are presented. Abstract: Citizens living in cities where public entities are committed to the development of city resilience are increasingly aware that the entire responsibility for preventing, responding to and recovering from crises cannot fully fall on public entities and private companies. In fact, citizens are more and more required to prepare for, respond to and recover from crises. To that end, there is an emerging need to involve not only public entities and private companies but also citizens in the process of building a city's resilience in order to understand the different perspectives on the same reality. This research paper is based on a systematic literature review to develop a framework that defines and describes the successful characteristics of public-private-people partnerships (4Ps) in the city resilience-building process. The framework revolves around two criteria for classification: the dimension of the characteristics (stakeholder relationship, information flow and conflict resolution), and the attributes of the partnership. A preliminary list of relationships among the characteristics found in the literature is also presented. The aim throughout is to define which characteristics need to be developed in order to better ensure successful cooperation among the three main stakeholders: public entities, private companies and citizens.